PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT HOMASINDO SUKSES ABADI - Supriandi, Supriandi; Simanjuntak, Jontro (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
This research aims to analyze if there is any influence from work motivation and discipline towards the performance of employees of PT Homasindo Sukses Abadi which engages in the field of currency exchange. The phenomenon of fluctuation of the performance of employees working for PT. Homasindo Sukses Abadi in Batam reflects the performance of employees has not been maximized. This research uses two independent variables which are discipline variable and work motivation variable. The technique used in collecting data used in this research is the distribution of questionnaire using purposive sampling method, whereby the population and sample used in this research are all the employees working for PT. Homasindo Sukses Abadi amounting to a total of 103 respondents. This research uses technical data analysis methods such as validity test, reliability test, classic assumption test, multiple linear regression analysis, determination coefficient test, and hypothesis test. The result of this research show that work discipline variable does have positive influence and is significant towards the performance of employees, so is the work motivation variable does have positive influence and is significant towards the performance of employees. Furthermore, work discipline and motivation variable simultaneously does have positive influence and is significant towards the performance of employees of PT. Homasindo Sukses Batam Abadi. Variables in this research have an influence od 55,4% towards the performance of employees. The rest 44,6% are influenced by other variables coming from outside of this research.Keywords: Work Motivation, Discipline, Employee Performance